In vitro effects of laser beam on antifungal activity of crude chloroform extract produce from leaves of concarups spp - hawraa Al-abedi; Dhurgham A. H. Alhasan; Thoalfiqar Ali Zaker (Basrah Journal of Veterinary Research)
The current study aimed to evaluate the effects of laser irradiation on the antifungal activity of the crude chloroform extract which was produced from leaves of Conocarpus species by which DMSO concentration (50 mg / ml) of this extract was exposed to laser radiation and other concentration was not exposed. Both concentrations were tested against the growth of Cryptococcus neoformans, Microsporum canis, Trichophyton mentagrophytes, and Rhodotorula mucilaginosa. Results showed that C. neoformans was sensitive only laser- exposed chloroform extract. While, the growth of other fungal species was unaffected either from non-laser - exposed chloroform extract or laser-exposed one. GC-MS analysis resulted in a content of the laser exposed crude chloroform extract form ⁅pyrazolo [1,5-a]pyrimidine-3-carbonitrile,2-methylthio-7-(2-pyridyl), ⁅benzaldehyde,2,4-bis(trimethylsil oxy),⁅3-hydroxymandelic acid, ethyl ester, di-TMS, and ⁅ pyrimidine-4,6(3H,5H)-dione, 2-butylthio-⁆ while non-laser exposed extract had ⁅ carbamic acid, methyl-, phenyl ester ⁆, ⁅ acetic acid, phenyl ester ⁆, ⁅ phenol ⁆, ⁅ pentadecanoic acid, methyl ester ⁆, ⁅ hexadecanoic acid, methyl ester ⁆, ⁅ methyl 8-methyl-nonanoate ⁆, ⁅ phytol, acetate ⁆, ⁅3,7,11,15-tetramethyl-2-hexadecen-1-ol ⁆, ⁅ citronellyl isobutyrate ⁆, ⁅ 5H-2a,4a,7a-triaza-7b-phosphacyclopent[cd]indene-7b-thione, 1,2,3,4,6,7-hexahydro-⁆, ⁅ olean-12-en-28-oic acid, 3-oxo-, methyl ester ⁆, ⁅4-amino-5,7-dichlorobenzofurazan ⁆, ⁅ phenol, 2,4-dichloro-6-nitro ⁆, ⁅ ⁆, ⁅ cyclobarbital ⁆, ⁅ benzo[h]quinoline, 2,4-dimethyl- ⁆, ⁅ pyrido[2,3-d]pyrimidine, 4-phenyl-⁆, ⁅ 1H-indole, 5-methyl-2-phenyl-⁆, and ⁅ carbonic acid, butyl octadecyl ester ⁆.